Comparative experimental and theoretical study of the rotational excitation of CO by collision with ortho- and para-D2 molecules. Issue 1 (30th November 2016) - Stoecklin, T.; Faure, A.; Jankowski, P.; Chefdeville, S.; Bergeat, A.; Naulin, C.; Morales, S. B.; Costes, M.
Abstract : A joint crossed beam and quantum mechanical investigation of the rotationally inelastic collisions of CO with ortho - and para -D2 molecules is reported. Abstract : A joint crossed beam and quantum mechanical investigation of the rotationally inelastic collisions of CO with ortho - and para -D2 molecules is reported. A new 4D potential energy surface (PES) averaged over the ground vibrational states of D2 and CO is used to calculate the rovibrational bound states of the ortho -D2 –CO complexes. Close coupling calculations are then performed in the rigid rotor approximation for ortho - and para -D2 colliding with CO for the experimentally investigated transition of CO ( j = 0 → 1) and for collision energies ranging from 0.1 to 25 cm −1 . The agreement between theory and experiment is found to be very good for both the bound state energies of the ortho -D2 –CO complexes and for the inelastic scattering cross-sections showing that the free rotation of two rigid rotors is a very good model of the D2 –CO system in this low collision energy domain.